Market Street view. - Gordon, John C. (photographer):::Creator::::::::::::
Elevated view of Market Street in San Jose, California. Photograph shows a park like scene with a few pedestrians walking on pathway. Vegetation and palm trees are seen on both sides of middle pathway along with the St. Joseph's Church across the street.